EFEKTIFITAS PEMBERIAN KOMBINASI AROMATERAPI PEPPERMINT DAN LEMON UNTUK MENGURANGI MUAL MUNTAH YANG BERLEBIHAN PADA IBU HAMIL TRIMESTER I DI PMB RONNI SIREGAR - Tarigan, Suci Nanda Resti; Parapat, Friska Margareth; Simanjuntak, Eva Hotmaria (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
One of the problems that occur during pregnancy that can increase the degree of pain is the occurrence of gestosis during pregnancy or diseases that typically occur during pregnancy, and one of the gestosis in pregnancy is hyperemesis gravidarum. The impact can occur on the mother and fetus. The purpose of this study was to determine the effectiveness of the combination of Peppermint and Lemonade Aromatherapy in reducing excessive vomiting nausea in 1st trimester pregnant women. This study uses a type of quantitative research with a Quasi-Experimental design with a Non Randomized Pretest Posttest Design. This research was conducted in December 2023 at the Midwifery Room of Medan Adventist Hospital. The sampling technique in this study was total sampling with a sample of 10 people. The instrument in this study used the observation sheet PUQE-24 Scoryng System. Based on researcher data from 10 respondents before the intervention was given, 6 of them experienced severe vomiting nausea and 4 respondents experienced moderate vomiting nausea and after the intervention there was a decrease in the level of vomiting nausea, namely 6 respondents with moderate vomiting nausea and 4 respondents experienced a decrease in mild vomiting nausea. The statistical test in this study used the Paired Sample T Test. The results of statistical tests with the Paired Sample Test obtained p values of 0.000 < 0.05. The conclusion of the results of this study is that the combination of peppermint and lemonade aromatherapy is effective in reducing excessive vomiting nausea in 1st trimester pregnant women.